2019
DOI: 10.1111/pere.12265
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept clarity and relationship satisfaction at the dyadic level

Abstract: Self‐concept clarity is an individual resource that is associated with couple relationship well‐being. In two dyadic studies, the authors investigated whether and how self‐concept clarity has implications for both partners' relationship satisfaction. Study 1 tested and supported the hypothesis that self‐concept clarity concurrently predicts own and partner's relationship satisfaction through couple identity in a sample of 202 dating couples. Study 2 tested and supported the hypothesis that self‐concept clarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 70 publications
(105 reference statements)
2
27
1
1
Order By: Relevance
“…The sample was composed of partners that generally reported to perceive the other as highly supportive (i.e., providing a high level of positive dyadic coping and a low level of negative dyadic coping), to successfully cope together with a common stressor, showing similar or slightly better dyadic coping abilities than reported in other Italian samples ( Donato et al, 2015 , 2018 ; Parise et al, 2018 ). Moreover, they reported high levels of relationship satisfaction, and average levels of couple generativity (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample was composed of partners that generally reported to perceive the other as highly supportive (i.e., providing a high level of positive dyadic coping and a low level of negative dyadic coping), to successfully cope together with a common stressor, showing similar or slightly better dyadic coping abilities than reported in other Italian samples ( Donato et al, 2015 , 2018 ; Parise et al, 2018 ). Moreover, they reported high levels of relationship satisfaction, and average levels of couple generativity (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As such, the present results expand our knowledge on couple identity processes. Researchers interested in the antecedents of couple identity have shown that individual differences (such as self-concept clarity, Parise et al, 2019), family characteristics (such as intrusive parenting, Manzi et al, 2015; Parise, Donato, Pagani, Ribeiro, & Manzi, 2015), relational factors (such as commitment, Lewandowski et al, 2010), and interpersonal processes (such as forgiveness, Karremans & Van Lange, 2008) contribute to its formation. In this work, we focused on the role of an important interpersonal process such as capitalization for the building and maintenance of couple identity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, potential moderators of the associations found should also be examined in future research. In particular, given the importance of individual differences in determining both capitalization and couple identity (e.g., depression, social anxiety, attachment orientations, or self-concept clarity; Hershenberg, Davila, & Leong, 2014; Kashdan, Ferssizidis, Farmer, Adams, & Mcknight, 2013; Parise et al, 2019; Shallcross, Howland, Bemis, Simpson, & Frazier, 2011), further studies could explore whether and how these characteristics may alter the capitalization process and its benefits for the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to research demonstrating the role of dyadic coping for partners’ relational well-being (e.g., Donato et al, 2015 ; Hilpert et al, 2016 ; Parise et al, 2019 ), abundant research has proven that coping positively as a couple in times of stress significantly reduces partners’ distress and improves partners’ psychological health, both when dealing with normative ( Molgora et al, 2018 , 2019 ; Alves et al, 2019 ) and non-normative life events ( Badr et al, 2010 ; Meier et al, 2011 ; Rottmann et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%